2010
DOI: 10.15288/jsad.2010.71.570
|View full text |Cite
|
Sign up to set email alerts
|

Affective and Personality Risk and Cognitive Mediators of Initial Adolescent Alcohol Use

Abstract: ABSTRACT. Objective: This study examined the role of cognitive factors-such as expectancies regarding the consequences of not drinking and perceptions of peer drinking-in mediating affective and personality-based risk associated with adolescents' decisions to initiate alcohol use. Method: Nondrinking high school students (N = 1,268) completed confi dential surveys on adolescent attitudes and behaviors related to substance use in 2 consecutive years. Self-reported alcohol use was assessed in both years, and soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 73 publications
2
31
0
Order By: Relevance
“…In control school districts, depressive symptoms were positively associated with beliefs that substance misuse has social benefits, perceptions that more of one’s friends and schoolmates misuse substances, and actual affiliation with peers who misuse substances. This confirms findings from observational studies of community samples [911]. In intervention school districts, many of these associations were significantly weaker.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In control school districts, depressive symptoms were positively associated with beliefs that substance misuse has social benefits, perceptions that more of one’s friends and schoolmates misuse substances, and actual affiliation with peers who misuse substances. This confirms findings from observational studies of community samples [911]. In intervention school districts, many of these associations were significantly weaker.…”
Section: Discussionsupporting
confidence: 86%
“…Indeed, compared with adolescents with fewer symptoms of depression, adolescents with more symptoms are more likely to believe that smoking cigarettes and drinking alcohol are common among their peers [9,10]. They also perceive that more of their friends smoke [11] and approve of smoking [12].…”
mentioning
confidence: 99%
“…Further, relative to non-distressed peers, depressed high school (Bekman et al 2010) and college students (Park and Levenson 2002) endorse stronger positive alcohol expectancies, and positive expectancies promote drinking to cope among college student drinkers (Goldsmith et al 2009). In a large adolescent sample, Kuntsche et al (2010) demonstrated that alcohol motives and expectancies are distinct constructs and, of all motives, coping motives emerged as the strongest mediator in the relationship between alcohol expectancies and alcohol outcomes (e.g., heavy drinking, consequences).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent risk-taking behavior is also more likely to occur in groups than that of adults (Chassin, Pitts, & Prost, 2002). In addition, perceptions of peer drinking (Arata, Stafford, & Timms, 2003;Bekman, Cummins, & Brown, 2010;D'Amico & McCarthy, 2006) and positive expectancies regarding alcohol (Goldberg, Halpern-Felsher, & Millstein, 2002) have been identified as risk factors for drinking in adolescence. These findings suggest that adolescent risk taking behaviors are socio-emotional in nature, indicating the need for prevention and intervention efforts that provide information that is socially and emotionally relevant to adolescents, as well as targeting normative beliefs and positive alcohol beliefs and expectancies.…”
Section: Introductionmentioning
confidence: 99%